IMPLEMENTASI TOTAL QUALITY MANAGEMENT DALAM MENINGKATKAN PRODUKTIVITAS KERJA DI LINGKUNGAN ORGANISASI PENDIDIKAN - Zulkarnaini Zulkarnaini (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Every educational organization is committed to continuing to advance, develop, and be able to survive in carrying out educational programs. For this reason, educational organizations must produce several service products with good quality, competitive prices with good service from their competitors. In addition, making continuous improvements in producing service production, namely by increasing work productivity with honest and professional work culture, effective promotions, and satisfying services for customers so as to be able to increase loyal costumers in obtaining sustainable service products. Therefore, comprehensive quality control is needed through the application of the Total Quality Management (TQM) concept. TQM is a management philosophy that focused on the need to know customer needs. The importance of taking the right action from the start, and recognizing that quality improvement will be achieved if the goals of all employees in educational organizations have become part of the overall organizational culture structure. This is because there is a close relationship between product quality and service, customer satisfaction, and profit organization. The higher the quality of a product, the higher the customer and at the same time, it will affect the reputation and electability of customers toward educational organizations. Therefore, the work productivity of educational organizations is a basic factor in considering improving the quality of education.